Ischemic Events Occur Early in Patients Undergoing Percutaneous Coronary Intervention and Are Reduced With Cangrelor: Findings From CHAMPION PHOENIX - Cavender, Matthew A.; Harrington, Robert A.; Stone, Gregg W.; Steg, Ph. Gabriel; Gibson, C. Michael; Hamm, Christian W.; Price, Matthew J.; Lopes, Renato D.; Leonardi, Sergio; Deliargyris, Efthymios N.; Prats, Jayne; Mahaffey, Kenneth W.; et al. (Circulation. Cardiovascular interventions, 2022)
Thrombotic events are reduced with cangrelor, an intravenous P2Y inhibitor. We sought to characterize the timing, number, and type of early events (within 2 hours of randomization) in CHAMPION PHOENIX (A Clinical Trial Comparing Cangrelor to Clopidogrel Standard of Care Therapy in Subjects Who Require Percutaneous Coronary Intervention). CHAMPION PHOENIX was a double-blind, placebo-controlled trial that randomized patients undergoing percutaneous coronary intervention to cangrelor or clopidogrel. For this analysis, we evaluated the efficacy of cangrelor in the first 2 hours postrandomization with regards to the primary end point (death, myocardial infarction, ischemia-driven revascularization, or stent thrombosis). Sensitivity analyses were performed evaluating a secondary, post hoc end point (death, Society of Coronary Angiography and Intervention myocardial infarction, ischemia-driven revascularization, or Academic Research Consortium definite stent thrombosis). The majority of events (63%) that occurred in the trial occurred within 2 hours of randomization. The most common early event was myocardial infarction; next were stent thrombosis, ischemia driven revascularization, and death. In the first 2 hours after randomization, cangrelor significantly decreased the primary composite end point compared with clopidogrel (4.1% versus 5.4%; hazard ratio, 0.76 [95% CI, 0.64-0.90], =0.002). Similar findings were seen for the composite end point of death, Society of Coronary Angiography and Intervention myocardial infarction, ischemia-driven revascularization, or Academic Research Consortium stent thrombosis at 2 hours (0.9% versus 1.6%; hazard ratio, 0.57 [95% CI, 0.40-0.80], =0.001). Between 2 and 48 hours, there was no difference in the primary composite end point (0.6% versus 0.5%; odds ratio, 1.17 [95% CI, 0.71-1.93]; =0.53). Early (≤2 hours of randomization) GUSTO (Global Use of Strategies to Open Occluded Coronary Arteries) moderate or severe bleeding events were infrequent, and there was no significant difference with cangrelor compared with clopidogrel (0.2% [n=10] versus 0.1% [n=4]; adjusted odds ratio, 1.41 [95% CI, 0.37-5.40]; =0.62). The reductions in ischemic events and overall efficacy seen with cangrelor in CHAMPION PHOENIX occurred early and during the period of time in which patients were being actively treated with cangrelor. These findings provide evidence that supports the importance of potent platelet inhibition during percutaneous coronary intervention. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT01156571.